2006 IEEE Conference on Emerging Technologies and Factory Automation 2006
DOI: 10.1109/etfa.2006.355417
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Agent-based Simulation Tool for Manufacturing Systems

Abstract: The application of Simulation to manufacturing has contributed to a generation of tools that is focused on specific problem solving related to automation, planning, material flow, supply chain, logistics,etc. Nowadays, manufacturing has evolved and its needs have changed. After an analysis of the current manufacturing simulation tools, we propose an approach based on Multiagent Systems theory, which covers current manufacturing needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…Ingalls [42] and Hicks [43] have emphasized for a hybrid optimization and simulation approach for strategic supply chain planning as this eliminates random trial and error method to obtain potential solutions. Ruiz et al [44] presented a classification of commercial simulation packages with their features and reported that meta-heuristics methods such as GA, tabu search, simulated annealing, and scatter search are commonly used to optimize the configuration decisions in simulation models. Jafferali et al [45] compared the optimization tools available in commercial simulation packages for scheduling.…”
Section: Supply Chain Simulationmentioning
confidence: 99%
“…Ingalls [42] and Hicks [43] have emphasized for a hybrid optimization and simulation approach for strategic supply chain planning as this eliminates random trial and error method to obtain potential solutions. Ruiz et al [44] presented a classification of commercial simulation packages with their features and reported that meta-heuristics methods such as GA, tabu search, simulated annealing, and scatter search are commonly used to optimize the configuration decisions in simulation models. Jafferali et al [45] compared the optimization tools available in commercial simulation packages for scheduling.…”
Section: Supply Chain Simulationmentioning
confidence: 99%
“…The lack of awareness about the potential of agent technology, concerns regarding MAS stability, scalability and survivability as well as missing standards, design and development tools have been seen as major obstacles that have to be overcome in order to achieve progress in the adoption of agent technologies [13]. Simulation is considered as effective method for testing different control architectures and improving the quality of solutions, which are in many cases closely related to control systems and scenarios in real life manufacturing [14].…”
Section: B Mas In Production Automationmentioning
confidence: 99%
“…This paper presents an extension of a previous work (Ruiz et al, 2006) in which a brief study was made to identify the manufacturing simulation process. The study distinguished two main phases in the simulation process of a manufacturing system: Model Creation and Model Simulation.…”
Section: A Mas Based Simulation Toolmentioning
confidence: 99%